The Fulfillment of Prisoners' Rights by Establishing Private Prisons as an Alternative to Prisoner Development is Reviewed from Law Number 22 of 2022 Concerning Corrections - Bramandita, Riki; Sofyan Gueci, Rizal; Hernamarwan Kristyanto, Gregorius (Pusat Publikasi Nusantara, 2023)
The problem of prisons in Indonesia has not been resolved until now. There are 3 (three) main problems to date, namely, Overcrowded Prisoners, Lack of Human Resources in Prisons and Large Costs. This greatly affects the rights of prisoners themselves, where the rights of prisoners have been regulated both in International (Standard minimum Rules For The Treatment Of Prisoner) and National provisions (Law Number 22 of 2022 concerning Corrections). This research aims to answer legal problems regarding how the government has been managing prisons and private prisons as an alternative solution to the problems of prisons in Indonesia. To answer the research problem, this study uses a type of normative legal research with a legal approach, concepts and comparisons. The data used are secondary data supported by primary, secondary and tertiary legal materials obtained through literature research or document studies. The results of this study show that in managing prisons, legally Indonesia has made significant improvements and more implemented the human rights system by changing the orientation of retaliation to coaching prisoners. However, in its implementation, the Indonesian government still finds it difficult to implement these noble intentions and until now there are 3 (three) major problems that have not been addressed, namely Overcrowded Prisoners, Lack of Human Resources in Prisons and Large Costs. To be able to implement these noble intentions, there is an alternative solution, namely the implementation of private prisons with the Public Private Partnership system or Hybrid System where this system has been successfully applied in France and produces efficiency for the state